Bearing the cost to witness: the political economy of risk in contemporary conflict and war reporting. (May 2018) - Creech, Brian
As journalistic work has become increasingly precarious in recent decades, exposure to risk – that is, true bodily harm – has become a normalized condition for those reporting from conflict zones. This article considers the political economy of risk, paying particular attention to the ways it has been constructed as a desirable and manageable condition for various classes of news workers. The burden of risk is distributed unequally across staff reporters, freelancers, and non-Western local journalists of all stripes, and a persistent discourse of witnessing obscures both these inequities and the structural conditions that allow news organizations to profit from an increased assumption of individual risk. As structural conditions, individual mitigations, and practices of textual commodification are considered and critiqued, the article concludes by identifying specific strategies that push beyond an economic logic, and thus reassert the cultural and political value of conflict and war reporting as a practice that merits protection, regardless of who produces it. Such a critique focuses on developing the discursive tools that allow journalists and outside observers alike to ask 'who should bear the costs of witnessing?'